The Impact of Transformational Leadership on Physicians’ Performance in China: A Cross-Level Mediation Model - Chu, Haiyun; Qiang, Binbin; Zhou, Jiawei; Qiu, Xiaohui; Yang, Xiuxian; Qiao, Zhengxue; Song, Xuejia; Zhao, Erying; Cao, Depin; Yang, Yanjie (Frontiers in Psychology, 2021)
Transformational leadership has been becoming increasingly vital to the provision of high-quality healthcare, particularly during major public health emergencies. The present study aims to investigate the impact of transformational leadership on physicians' performance and explore the cross-level underlying mechanisms with achievement motivations and coping styles among Chinese physicians. During 2017-2019, 1527 physicians of 101 departments were recruited from 6 hospitals in China with a cluster random sampling method. Participants completed several questionnaires regarding their job performance, achievement motivations, coping styles, and transformational leadership. Multilevel mediation effects were tested using cross-level path analysis. The result of this study indicated that transformational leadership was applied well in Chinese medical settings with a score of (101.56 ± 6.42). The hierarchical linear model showed that transformational leadership had a cross-level direct positive effect on physicians' performance (β=1.524, p<0.05). Furthermore, results of cross-level path analyses revealed that transformational leadership contributed to physicians' performance by sequentially influencing achievement motivations first and then coping styles. In addition, the path “transformational leadership → positive coping style → physicians' performance” showed the strongest cross-level indirect effect. In summary, public health leaders should enhance physicians' performance by promoting individual development, especially achievement motivation and positive coping style.